The Status of the Adoption of Mangrove Swamp Rice Varieties in Sierra Leone - Gborie, Moses; Mahmood, Nazir A; Kanu, Adam S; Jenkins, Finda B; Kargbo, Henry M.S (Asian Journal of Agriculture and Rural Development, 2016)
Mangrove swamp rice varieties developed at the Rokupr Agricultural Research Centre (RARC), Sierra Leone were evaluated in 2014 to determine their adoption status in Kambia, Port Loko and Moyamba districts of Sierra Leone. The study evaluated farmers’ knowledge about the varieties, the varieties grown by farmers at least once, adopters, non-adopters, loss of varieties, abandonment of varieties, and the determinants of the adoption of mangrove rice varieties. Data were obtained from a sample survey of 600 mangrove rice farmers using the multistage stratified random sampling technique. Farmers in the Kambia district were more knowledgeable about the mangrove varieties: ROK 5 and ROK 10 are the most adopted varieties while ROK 5, ROK 10 and CP 4 are the most cultivated and have been grown at least once by some farmers in all the districts – ROK 5 (380 farmers); ROK 10 (315 farmers); and CP 4 (99 farmers). Probit regression estimation shows that farmers’ adoption of the mangrove rice varieties was affected positively and significantly by farmers’ level of education, training, access to credit, farm size, contact with extension, and farming experience.